Pemberdayaan kelompok pengrajin keripik tempe dalam upaya optimalisasi produksi menggunakan mesin pemotong dan penggoreng otomatis di Paguyuban Plaju Bersinar Kota Palembang - Shomedran, Shomedran; Nurrizalia, Mega; Dwi Kurniawan, Elfahmi; Maryani, Maryani (IKIP SILIWANGI, 2025)
The group of Tempe craftsmen at Paguyuban Palju Bersinar is currently continuing despite the obstacles they face, such as unstable raw material prices, unstable selling prices, and the production of various foods from Tempe such as Tempe chips is also not optimal. This is because production is still done manually, thus affecting the production amount. So far, the focus is only on Tempe production, so there is a need for alternative solutions that can help members of the Tempe craftsmen to survive and increase their income. It is hoped that the use of a Tempe cutting machine can help craftsmen, especially in making Tempe chips, so that they get better production. The goal to be achieved from this community service is to empower people using cutting and frying tools, so that after training the craftsmen are able to produce their own Tempe chips and increase production quantities, ultimately they are able to sell their products more widely. There were 24 participants in this activity who were members of the Plaju Bersinar Association. The methods used were delivery of material, direct practice and training as well as pre-test and post-test evaluation, and monitoring. This activity showed that the participants were quite enthusiastic and gained knowledge and skills in using cutting and frying machines.